2004
DOI: 10.3168/jds.s0022-0302(04)73441-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among International Body Condition Scoring Systems

Abstract: Scoring body condition and assessing changes in the body condition of dairy cattle have become strategic tools in both farm management and research. Consequently, body condition score (BCS) is being researched extensively throughout the world. However, international sharing, comparing, and use of data generated are limited because different BCS systems exist. In the United States and Ireland a 5-point BCS system is used for dairy cows, whereas Australia and New Zealand use 8- and 10-point scales, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
260
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(280 citation statements)
references
References 8 publications
9
260
4
7
Order By: Relevance
“…Chagas et al (9) showed a negative relationship between BCS at calving and its changes in the early lactation and the duration of return to ovarian activity, connected with reduced LH secretion and lowered ovarian follicle excitability to the action of gonadotropic hormones. In the opinion of Roche et al (25), a loss of more than 0.5 BCS during early lactation reduces the chance of successful insemination in the first 6 weeks after calving, which was not confirmed in this study. However, it was shown that the body condition on the dry-off day had a statistically significant effect on the insemination index in herd B.…”
Section: Discussioncontrasting
confidence: 55%
“…Chagas et al (9) showed a negative relationship between BCS at calving and its changes in the early lactation and the duration of return to ovarian activity, connected with reduced LH secretion and lowered ovarian follicle excitability to the action of gonadotropic hormones. In the opinion of Roche et al (25), a loss of more than 0.5 BCS during early lactation reduces the chance of successful insemination in the first 6 weeks after calving, which was not confirmed in this study. However, it was shown that the body condition on the dry-off day had a statistically significant effect on the insemination index in herd B.…”
Section: Discussioncontrasting
confidence: 55%
“…Body condition score may be less accurate in thin cows with little subcutaneous fat, and it may be more difficult to assess subcutaneous fat levels accurately in obese cows (Roche et al, 2009). Nevertheless, fewer animals are at the extremes of the BCS scale (Ruegg and Milton, 1995;Roche et al, 2004;Berry et al, 2007), and Schröder and Staufenbiel (2006) summarized from various studies that a 1-unit change in BCS consistently correlated with about 50 kg of empty body fat. Additionally, Waltner et al (1994) reported a strong correlation between BCS and observed body fat.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a quick, non-invasive, inexpensive, visual and tactile way of assessing the degree of fatness of dairy animals 2 and it is recognized by the animal scientists and producers as an important factor in dairy bovine management. 3 Optimal body condition of dairy cow is important for obtaining elite herd and quantity milk production because low or excessive body energy reserve may have a greater risk of lower milk yield and higher milk somatic cell count, SCC.…”
Section: Introductionmentioning
confidence: 99%